Berberisms in el-Gəblä hassāniyyä Arab dialect - Ould Mohamed Baba, Ahmed-Salem (Anaquel de Estudios Árabes, 2004)
Repertoire of the main voices of berber origin in el-Gəblä hassāniyyä Arab dialect, organized according to the most commun morphological schemes.
Keywords: Arabic dialectology; Sanhā ğ ä bereber dialect; Hassaniyyä dialect; Lexicography